A research investigation into the impact of ensuring workplace safety and worker protection among staff at Square Pharmaceuticals PLC, Bangladesh - Alam, Shahriar; Majumder, Mushfiq Mahmud; Barna, Samiha Ibnat; Yshan, Chowdhury Shafin Sahil; Islam, Ahsanul; Akther, Mahima (BRAC University Research For Development Club (BURED), 2024)
Cataloged from PDF version of the article.